Variabilité hydrologique et vulnérabilité des populations du Lago Janauaca (Amazonas, Brésil) - Guillaume Drapeau; Catherine Mering; Josyane Ronchail; Naziano Filizola (Confins, 2011)
Closely related to the seasonal flood pulse of the Amazon River, the activities of várzeas farmers and fishermen are particularly sensitive to the critical events of hydrological variability. This paper analyzes the vulnerability of riverine communities to extreme high and low waters around the Lago Janauaca near Manaus, in a context of intensification of the hydrological cycle. We shall first try to characterize the hydrological variability of Rio Solimões and its spatial impact on the Lago. Important though is the extension of the natural phenomenon, human dynamics on the banks of the lake must be also taken into consideration. Such dynamics are due to the opening of dirt roads linking the lake to the BR319, rather than to the moderate expansion of traditional crops. Finally, interviews with inhabitants reveal a complex relationship between the various activities and hydrological extremes. Droughts appear to be the major disturbances, not only because of their impact on crops, but mostly because of the difficulties they imply for local and regional mobilities.